Modified Boundary Condition for Membrane Wall Concentration Prediction in Narrow Membrane Channel - Ahmad, A. L.; Lau, K. K.; Abu Bakar, M. Z.; Abd. Shukor, S. R. (Journal of Applied Membrane Science & Technology, 2017)
The efforts of CFD simulation study to reveal the membrane wall concentration in the membrane channel which consider hydrodynamics and permeation properties are found to be inadequate. Hence, the ultimate objective of this paper is focusing on the employment of modified boundary condition to model the membrane interface in the membrane channel. Permeation properties such as permeation flux and concentration have been integrated in this modified boundary condition. Commercial CFD simulation package has been utilized to predict the membrane wall concentration for different transmembrane pressure and feed Reynolds number in the membrane channel. The simulated results were validated and compared with the published data from literature, showing a satisfactory agreement. This study has proven the increment in feed Reynolds number can enhance the mass transfer rate and suppress the formation membrane wall concentration. The utilization of modified boundary condition has promoted the accuracy and capability of commercial CFD simulation package to model and predict the hydrodynamics and permeation phenomenon in the membrane channel.